Implementation of Flutter-based Learning Management System (LMS) at Universitas Andi Djemma Palopo - Aishiyah Saputri Laswi; Apriyanto Apriyanto; Amiul Amruh A.M. (Faculty of Engineering, Andi Djemma University, 2022)
Learning Management System (LMS) is a tool that is essential to redound an interaction between instructor and the learners and considering the technology headway nowadays (gadget). Therefore, research has been made to develop an LMS application for mobile devices in Universitas Andi Djemma Palopo, especially in the informatics engineering department using the Flutter framework. The method used for this research is RD which stands for Research and Development with ADDIE Development Model, Analysis, Design, Development, Implementation, and Evaluation. The result of this research is known: 1) This application (LMS) made using the Flutter framework and Firebase database simplifies the development process; 2) This application was made for the informatics engineering department, Universitas Andi Djemma Palopo. This mobile app has several useful features, including making a class, class discussion, making subjects, assignments, and attendance; 3) The LMS implementation uses a questionnaire based on usability and has been obtained with an eligibility percentage of 83.03%. The app has been declared as very feasible based on the eligibility percentage.